Mecanismos de regulação da via de sinalização Wnt pela E3 ubiquitina ligase SCF(Fbxo7) - Oliveira, Caio Almeida Batista de (2019)
SCF complexes are composed by Skp1, Cullin1, Rbx1 and an F-box protein (FBP), which are responsible to give specificity to the complexes, as they interact with substrates, allowing ligation of an ubiquitin molecule to the target. Fbxo7 forms the fifth most abundant SCF complex in cells, however there are few described targets of its complex, which does not explain its biological functions. Mutations in PARK15 gene, which codes for Fbxo7, are related to Parkinson’s Disease and deregulation on Fbxo7 levels to cancer. Recently, we demonstrated Fbxo7 activates Wnt pathway and has as targets GSK3β and potentially β-TrCP, two regulator proteins of this pathway, which controls genes involved in cellular proliferation and differentiation, being directly associated to tumour development. Therefore, the aim of this work was to understand how SCF(Fbxo7) is modulating Wnt signalling pathway. Point mutations were inserted in two (K292R and K297R) or three (K292R, K297R and K303R) residues in GSK3β, in order to prevent its ubiquitination by Fbxo7. Similarly to GSK3β, mutants interact with Fbxo7 as there are no structural alterations as demonstrated by in silico analysis. However, surprisingly, point mutations elevated mutants ubiquitination signal in comparison to GSK3β. Interaction and ubiquitination profiles were also assessed for GSK3β in its phosphorylation sites (S9 and Y216). Although Fbxo7 keeps interacting with versions S9A and Y216F, GSK3β-S9A presents an abrupt reduction in its ubiquitination signal while GSK3β-Y216F was more ubiquitinated compared to GSK3β. It was performed interaction and ubiquitination assays for Fbxo7 and β-TrCP, showing their interaction is mediated via Fbxo7 N-terminal and suggesting β-TrCP is a target of Fbxo7. Stability assays demonstrated Fbxo7 alters levels only of GSK3β-Y216F, in comparison to GSK3β, GSK3β-S9A and β-TrCP. It was also observed that even though it ubiquitinates proteins involved in Wnt pathway, Fbxo7 does not alter the levels of effector molecule of this pathway, β-catenin. Finally, results showed Fbxo7 avoids GSK3β recruitment to cellular membrane fraction compared to Fbxo7-ΔF. Overall, this work suggests a new mechanism of Wnt activation through GSK3β ubiquitination dependent of Serine 9 residue, which prevents its migration to the cell membrane.